Therapy of Type 2 diabetes: more gliflozines and less metformin?. (21st April 2023) - Verdecchia, Paolo; Murdolo, Giuseppe; Coiro, Stefano; Santucci, Andrea; Notaristefano, Francesco; Angeli, Fabio; Cavallini, Claudio
Abstract: Metformin is a frequently used anti-diabetic drug. In addition to the well-known modulating properties on glyco-metabolic control, metformin reduces cardiovascular (CV) risk partly independently of its anti-hyperglycaemic effect. The use of 'new' anti-diabetic drugs, inhibitors of the renal Na-glucose co-transporter (SGLTs-I or 'gliflozines') and GLP-1 receptor agonists (GLP1-RAs), has further contributed to challenge the strictly 'gluco-centric' view of diabetic CV disease. Several controlled trials have demonstrated that the cardio-renal benefits of gliflozines and GLP1-RAs are present regardless of the presence of metformin as 'background' therapy. The impact on the 'cardio-renal continuum' exerted by SGLTs-I was also noted in non-diabetic patients with heart failure and reduced or preserved ventricular function and different levels of renal function. These drugs reduced re-hospitalization, CV mortality, and progression to end-stage renal disease. These clinical acquisitions, implemented by Scientific Societies, have led to a change in the therapeutic approach to diabetic cardio-renal disease. Although metformin still represents a valid therapeutic option to be offered particularly to 'naïve' diabetic patients without previous cardio-renal events, SGLTs-I and/or GLP1-RAs emerge as 'first-line' drugs in diabetic patients with previous CV events, or at high CV risk, without having to request 'on board' metformin therapy.